REFRAMING THE LECTURER’S ROLE IN THE AGE OF GENERATIVE AI: TOWARDS A HUMAN–AI CO-TEACHING MODEL IN DESIGN EDUCATION - Hapiz, Hana Yazmeen; Ibrahim, Yuhanis; Abdul Latef, Azlin Sharina; Ahmad, Nooraziah; Mohamad, Darliana; Radzuan, Ainul Wahida (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
Generative artificial intelligence (Gen-AI) has rapidly entered design studio practice, enabling students to produce visual concepts, models, and narratives with unprecedented speed and variety. While these tools expand creative possibilities, they simultaneously challenge traditional pedagogical assumptions regarding originality, authorship, and the role of the lecturer. This study explores the potential of Human–AI Co‑Teaching Models in design studio pedagogy, focusing on how lecturers’ roles evolve when Gen‑AI becomes an active partner in the creative process. Using case studies from design studios in higher education, the research adopts a qualitative action‑research approach with lecturers and students engaging in AI‑augmented studio projects. Findings highlight a paradigm shift: the lecturer’s role transitions from knowledge gatekeeper to critical guide, curator, and ethics negotiator. The paper proposes a framework for Human–AI Creative Pedagogy that balances efficiency and innovation with reflection, ethics, and critical thinking. Implications are offered for design education governance, studio assessment models, and lecturer training in the age of Gen‑AI.